Edukasi Terapi Sentuhan Lembut (Gentle Touch Therapy) sebagai Upaya Stimulasi Tumbuh Kembang Bayi - Susmita Susmita; Juni Harista (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Infant growth and development are crucial issues that require serious attention, particularly during the early childhood phase, which is crucial for a child's future development. The golden age of infants is the most sensitive period to various forms of stimulation that influence their motor, sensory, cognitive, and emotional development. However, not all parents, especially mothers, fully understand the importance of appropriate and safe stimulation in supporting infant growth and development. One form of stimulation that is relatively easy to perform, has no side effects, and can be applied independently at home is gentle touch therapy. Gentle Touch Therapy is a complementary therapy method that involves gentle, affectionate touch on the baby's body, aimed at stimulating the nervous system, strengthening the emotional bond between mother and child, and increasing comfort and relaxation in the baby. Several studies have shown that this gentle touch can improve sleep quality, accelerate weight gain, relieve stress, and encourage infant neuromotor and socio-emotional development. This community service activity was carried out as an effort to increase mothers' awareness and skills in providing stimulation through gentle touch. The activity was carried out at the Andina Independent Midwife Practice (PMB), Palembang City, in June 2025. The main target of this activity was mothers with babies aged 0–12 months. The implementation method included providing education through interactive lectures, demonstrations of touch therapy techniques by health professionals, and direct practice by mothers accompanied by facilitators. The results of the activity showed a significant increase in mothers' understanding of the importance of growth and development stimulation, especially through gentle touch therapy. The participants showed high enthusiasm in participating in the activity and were able to practice gentle touch techniques correctly and confidently.